Peran Mediasi Efikasi Diri Pada Pengaruh Ekosistem Kewirausahaan Terhadap Niat Berwirausaha Kalangan Santri Banyuwangi - Raka Malik Azid (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2023)
The increase in the unemployment rate in Banyuwangi Regency is caused by a lack of job opportunities. So that entrepreneurship is the best choice in overcoming the lack of jobs. This study intends to examine the effect of the entrepreneurial ecosystem on students' entrepreneurial intentions both directly and indirectly with self-efficacy as a mediating variable. This research is included in the type of quantitative research using an explanatory research approach. Data was collected through an online questionnaire survey using a Google form which was distributed to Darussalam Blokagung students. The hypothesized relationship was tested with data collected from 259 respondents with a sampling technique using the Isaac and Michael formula. The Analysis Tool uses SmartPLS 3.0. The results of the study prove that the entrepreneurial ecosystem influences students' self-efficacy positively and significantly. Entrepreneurial ecosystem and partial self-efficacy have a direct effect with a significant positive direction on entrepreneurial intentions. Furthermore, this study found that self-efficacy has a mediating effect in a significant positive way between the entrepreneurial ecosystem and entrepreneurial intentions. The findings of this study have several practical implications for the management of the Darussalam Blokagung Islamic Boarding School in entrepreneurship education. This study also contributes to the emerging literature on the entrepreneurial ecosystem, self-efficacy and entrepreneurial intention.